Autologous Hematopoietic Stem Cell Transplantation for Behçet’s Disease: A Retrospective Survey of Patients Treated in Europe, on Behalf of the Autoimmune Diseases Working Party of the European Society for Blood and Marrow Transplantation - Puyade, Mathieu; Patel, Amit; Lim, Yeong Jer; Blank, Norbert; Badoglio, Manuela; Gualandi, Francesca; Ma, David D.; Maximova, Natalia; Greco, Raffaella; Alexander, Tobias; Snowden, John A. (Frontiers in Immunology, 2021)
Background Behçet’s Disease (BD) is an autoimmune disease mostly presenting with recurrent oral and genital aphthosis, and uveitis. Patients are rarely refractory to immunosuppressive treatments. Autologous hematopoietic stem cell transplantation (aHSCT) is a standard of care in other autoimmune diseases. Some patients with BD have been treated with aHSCT based on compassionate use. Objectives Evaluate the outcome of aHSCT in adult patients with BD treated in member centers of the European Society for Blood and Marrow Transplantation (EBMT). Methods Adults who received aHSCT primarily for BD were identified retrospectively in the EBMT registry and/or in published literature. Data were extracted from either medical records of the patient or from publications. Results Eight out of 9 cases reported to the registry and extracted data of 2 further patients from literature were analyzed. Four were female, median age at onset of BD was 24y (range 9-50). Median age at aHSCT was 32y (27-51). Patients had received median 4 (2-11) previous lines of therapy (89% corticosteroids, 50% methotrexate, anti-TNFα therapy or cyclophosphamide). All patients had active disease before mobilization. Conditioning regimen was heterogeneous. Median follow-up was 48 months (range 6-240). No treatment-related mortality was reported. This procedure induced complete remission (CR) in 80%, partial remission in 10% and lack of response in 10% of the patients. Relapse rate was 30% (2 relapses in patients in CR and 1 relapse in the patient in PR) with panuveitis (n=1), aphthosis (n=2) and arthralgia (n=1). Six patients were in CR. No late complications were reported. Conclusion aHSCT has an acceptable safety profile and represents a feasible and relatively effective procedure in severe and conventional treatment-resistant cases of BD and has the potential to stabilize BD in patients with life-threatening involvements.